2022
DOI: 10.1161/circulationaha.121.056892
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Metabolome and White Matter Hyperintensities in Women and Men

Abstract: Background: White matter hyperintensities (WMH) are identified on T2-weighted magnetic resonance images of the human brain as areas of enhanced brightness; WMH are a major risk factor of stroke, dementia, and death. Currently, there are no large-scale studies testing associations between WMH and circulating metabolites. Methods: We studied up to 9,290 individuals (50.7% females, average age 61 years) from 15 populations of 8 community-based cohorts. WMH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 90 publications
4
19
0
Order By: Relevance
“…62 While this may reflect recruitment bias seen in many hospital-based stroke treatment trials that include neuroimaging for cSVD, it may also imply that males develop higher cSVD severity, especially in stroke presentations which may, in turn, reflect male: female ratio differences in metabolomic. 63 Conversely, the male: female ratio did not predict cSVD prevalence in this meta-analysis, possibly due to the diluting effect of community-based studies in which cSVD prevalences are low.…”
Section: Discussionmentioning
confidence: 59%
“…62 While this may reflect recruitment bias seen in many hospital-based stroke treatment trials that include neuroimaging for cSVD, it may also imply that males develop higher cSVD severity, especially in stroke presentations which may, in turn, reflect male: female ratio differences in metabolomic. 63 Conversely, the male: female ratio did not predict cSVD prevalence in this meta-analysis, possibly due to the diluting effect of community-based studies in which cSVD prevalences are low.…”
Section: Discussionmentioning
confidence: 59%
“…Our findings were observed for sphingomyelins in particular, a subclass that are especially abundant in the CNS, where they form pivotal components of neuronal membranes and play key roles in signal transduction (49). Given their biological role, it is unsurprising that sphingolipids have been previously linked to brain health and pathology (50,51). Here, we report associations between a module enriched in sphingolipids and hippocampal volume, as well as several sphingomyelin hub metabolites and whole-brain volume.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Sliz et al, individual vascular risk factors such as hypertension explained 1% or less of the variance of WMH in each of their cohorts. 2 Analysis of other cohorts has also found that conventional vascular risk factors explain 2% or less of the variation in WMH. 5 In contrast, conventional vascular risk factors and age account for more than half of the variance in carotid atherosclerotic plaque.…”
Section: Article See P 1040mentioning
confidence: 99%
“…7 Using these methods, they were able to test 2217 metabolites and lipoproteins in serum from participants in 8 community-based cohort studies. 2 Accounting for multiple hypothesis testing using the false discovery rate method, they found associations between WMH and hydroxyphenylpyruvate (an amino acid metabolite), glucose metabolism products, lipids, cell membrane components (lysophosphatidylcholines), and myelin components (hydroxysphingomyelins). It is interesting, but of unclear significance, that they also found evidence of modification by sex, with most associations significant in men only.…”
Section: Article See P 1040mentioning
confidence: 99%